Investigation on group delay ripple effects and the hybrid approach for optical beamforming - Pham, Quang Thai (2011)
The thesis investigated on the negative effects of group delay ripples in optical beamformers using chirped grating. Also, the hybrid beamformer based on two prominent optical beamorming approaches was proposed. The hybrid scheme overcome the disadvantages and emphasized the advantages of both approaches. Moreover, the hybrid scheme subdued the negative effect of group delay ripples. Several modifications of the hybrid scheme for different applications were also proposed.